Labile and refractory fractions of sedimentary organic carbon off the Changjiang Estuary and its implications for sedimentary oxygen consumption - Cao, Yu; Huang, Hong; Zhao, Xu; Li, Jun; Wang, Teng; Lin, Jun; Zhu, Zhuo-Yi (Frontiers in Marine Science, 2023)
In large river-affected estuaries and adjacent seas, there is minimal evaluation of the labile and refractory fraction of sediments and further a lack of attention to the corresponding potential in dissolved oxygen utilization. In this study, we collected sediment samples from the Changjiang estuary and adjacent coastal areas in the East China Sea in June 2019 to reveal the distribution, main controlling factor, and implications of four operational fractions of sediment organic carbon that range from labile to refraction. The four operational fractions of sedimentary organic carbon include 1) water extractable carbon (WEC), 2) salt extractable carbon (SEC), 3) chloroform extractable carbon (MBC), and 4) refractory organic carbon (ROC). The bulk sedimentary organic carbon (SOC), WEC, SEC, MBC, and ROC were 9.43 ± 3.07 g/kg, 0.12 ± 0.10 g/kg,0.16 ± 0.07 g/kg, 1.58 ± 0.45 g/kg, and 4.38 ± 1.95 g/kg, respectively. Labile organic carbon (LOC), namely WEC+SEC, increases along with increasing SOC. MBC showed a clear seaward decreasing pattern, whereas the refractory SOC on the opposite showed a seaward increase pattern off the Changjiang Estuary. Grain size plays a vital role in constraining the LOC fractions, and samples from aquaculture areas showed extra-higher levels of LOC when compared to the non-aquaculture area. The depth of hypoxia in the near bottom waters, which would be caused by a total decomposition of 4 mm of LOC in the sediment, ranged between 0.3m to 4.7m with an average depth of 2 m.